Attributes of senior-friendly tourism destinations for current and future senior tourists: an importance-performance analysis approach - Liew, Sien Leong; Hussin, Siti Rahayu; Abdullah, Nawal Hanim (SAGE Publications, 2021)
This study aims to identify the tourists’ expectation and satisfaction of destination attributes from the perspective of senior tourists in Malaysia. Two groups of tourists were chosen as the study sample, that is, future seniors (40–54 years old) and seniors (55 years old and above). It is hoped that, through recognizing and raising awareness on the need for equal traveling opportunities, senior tourists and future senior tourists will be encouraged to undertake more tourism activities. An importance-performance analysis (IPA) and paired sample t tests were employed to investigate senior tourists’ perceptions of senior-friendly destination attributes. Measures of destination attributes included the “4As” (i.e., attractions, accessibility, amenities, and ancillary services). The findings from a survey of 227 respondents revealed that the most important attributes for a senior-friendly destination are safety and cleanliness. Other attributes deemed important by senior tourists include the availability of leisure facilities and barrier-free public transportation. The findings also highlight attributes that tourism industry practitioners may use to improve tourists’ satisfaction and develop into competitive advantages against other tourist destinations. Both theoretical and practical implications of these important findings are discussed.